Analysis Of Food Waste Management Strategies At Pandora Lounge Gading Serpong - Christoper, Stanley Gracius; Pujiastuti, Sri (Politeknik Internasional Bali, 2025)
This qualitative study aims to analyze the strategies and effectiveness of food waste management in the kitchen operations of Pandora Lounge Restaurant, highlighting the issue of food waste as a critical concern in Indonesia's tourism sector. Data was collected through interviews with the Owner and Head Chef, observations, and documentation, and then analyzed using the Miles and Huberman model and SWOT evaluation. The research findings reveal that the food waste management strategies at the restaurant are not yet optimal, with strengths in the reuse of leftover ingredients and the separation of halal or non-halal waste, but limited by major weaknesses such as the absence of written standard operating procedures (SOPs), limited processing equipment, and insufficient staff awareness of the 3R methods (Reduce, Reuse, Recycle). While opportunities for collaboration with third parties and government incentives remain untapped, threats such as stricter regulations and competition from more environmentally friendly restaurants need to be addressed. The study concludes that a more systematic and integrated approach is essential, through the development of SOPs, technological investments, and staff training, to enhance the effectiveness of food waste management in support of sustainable tourism.